Επικοινωνιακές προκλήσεις στην εκπαίδευση χωρίς αποκλεισμούς που αντιμετωπίζουν κωφά και μη κωφά άτομα (University of Maribor Press, 2022)
Communication Challenges in Inclusive Education Faced by Deaf and Non-deaf People. This is a consolidated report on the work done in Intellectual Output One: Communication Challenges for the Advancing Inclusive Education Through International Sign - InSign project. This report combines and summarises the results obtained in national reports done by project partners from Cyprus, Germany, Greece, Portugal, and Slovenia. This document includes information on national sign languages, support for deaf people and their learning possibilities in different countries. In one section, we will review the status of International Sign in all the partner countries. We have also performed surveys done primarily with students to measure how they perceive deaf people, how they understand sign language and the difficulties deaf face in the education system. In this document, we analyse the data collected across the project partners. Each partner has also performed a guided interview with those most familiar with the deaf community (deaf themselves, educators, interpreters etc.) to help better understand the circumstances and answer some of the questions difficult to find in literature. The Consolidated Report summarises interview findings from national reports with the main takeaways.